Respuesta :

Answer:

q=0

r=2

s=3

t=-3

Step-by-step explanation:

q represents the value we should get from evaluating d(-8).

[tex]d(x)=-\sqrt{\frac{1}{2}x+4}[/tex]

To find d(-8) we use this function here labeled d and replace x with -8:

[tex]d(-8)=-\sqrt{\frac{1}{2}(-8)+4}[/tex]

[tex]d(-8)=-\sqrt{-4+4}[/tex]

[tex]d(-8)=-\sqrt{0}[/tex]

[tex]d(-8)=0[/tex]

So q is 0 since d(-8)=0.

r represents the value we should get from evaluating f(0).

[tex]f(x)=\sqrt{\frac{1}{2}x+4}[/tex]

To find f(0) we use this function labeled f and repalce x with 0:

[tex]f(0)=\sqrt{\frac{1}{2}(0)+4}[/tex]

[tex]f(0)=\sqrt{0+4}[/tex]

[tex]f(0)=\sqrt{4}[/tex]

[tex]f(0)=2[/tex]

So r is 2 since f(0)=2.

s represents the value we should get from evaluating f(10).

[tex]f(x)=\sqrt{\frac{1}{2}x+4}[/tex]

To find f(10) we use this function labeled f and replace x with 10:

[tex]f(10)=\sqrt{\frac{1}{2}(10)+4}[/tex]

[tex]f(10)=\sqrt{5+4}[/tex]

[tex]f(10)=\sqrt{9}[/tex]

[tex]f(10)=3[/tex]

So s is 3 since f(10)=3.

t represents the value we should get from evaluating d(10).

[tex]d(x)=-\sqrt{\frac{1}{2}x+4}[/tex]

To find d(10) we use the function labeled d and replace x with 10:

[tex]d(10)=-\sqrt{\frac{1}{2}(10)+4}[/tex]

[tex]d(10)=-\sqrt{5+4}[/tex]

[tex]d(10)=-\sqrt{9}[/tex]

[tex]d(10)=-3[/tex]

So t is -3 since d(10)=-3

q=0

r=2

s=3

t=-3